Consistency Between NASS Surveyed Soil Moisture Conditions and SMAP Soil Moisture Observations. Issue 9 (6th September 2019) - Colliander, Andreas; Yang, Zhengwei; Mueller, Rick; Sandborn, Avery; Reichle, Rolf; Crow, Wade; Entekhabi, Dara; Yueh, Simon
Abstract: The U.S. Department of Agriculture National Agricultural Statistics Survey (NASS) collects and publishes crop growth status and soil moisture conditions in major U.S. agricultural regions. The operationally produced weekly reports are based on survey information. The surveys are based on visual assessments and—in the case of soil moisture—report soil moisture levels in one of four categories (Very Short, Short, Adequate, and Surplus). In this study, we show that these reports have remarkable correspondence with the National Aeronautics and Space Administration Soil Moisture Active Passive (SMAP) Level‐4 Soil Moisture (L4SM) product. This consistency allows for combining the two different types of data to produce a value‐added assessment, which enables cropland soil moisture mapping and state‐level statistics. Moreover, it enables daily assessment rather than weekly. In this study classification thresholds are derived for L4SM by mapping cumulative distribution functions of L4SM surface and root zone SM to the categorical NASS SM conditions. The results show that, year over year, the SMAP cumulative SM distributions are consistent with the NASS SM conditions and, furthermore, that the temporal evolution of the SMAP‐derived thresholds is consistent with the seasonal crop growth cycles from year to year. The results signify that the SMAP SM retrievals are relatable to SM estimation conducted in agricultural crop land by land managers and farmers, which underlines the general applicability of the SMAP data. Key Points: USDA NASS surveyed soil moisture has a remarkable correspondence with the soil moisture measured by NASA's SMAP mission The consistency allows a production of a value‐added combination of the two data sets The combination features mapped fields rather than state‐by‐state tables, and it is refreshed daily rather than weekly